Early Cenozoic exhumation of the Nanling Mountains (South China): a response to extensional tectonics and Asian monsoon intensification - Junjie Wang; Pengfei Li; Christoph Glotzbach; Dewen Zheng; Chaopeng Li; Yuntao Tian; Cunwei Lin; Guanglin Wang; Yulian Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Flexible, ultrastrong, and recyclable polymer/CNT/carbon fiber fabric composites for high-performance electromagnetic interference shielding - Yuna Wang; Caiyun Liang; Chuanwei Lin; Jiadong Li; Yongjiu Liang; Xiangdong Liu; Dewen Dong (Chemical Engineering Journal, 2026)

An efficient framework of nonlinear hysteresis analysis for multi-bolt connections via improved Iwan model and CG-FFT - Tengfei Wu; Jian Xing; Qiangqiang Zhao; Dewen Yu; Qiyin Lin; Jie Xiao; Jun Hong (Engineering Structures, 2026)

Monthly Soil Respiration in China's Forests: Spatiotemporal Patterns and Drivers Over 21 Years - Jiaming Chang; Ni Huang; Li Wang; Luying Zhu; Xiaoyu Lin; Jie Liu; Zheng Niu; Dewen Cai (Global Change Biology, 2026)
Forests play a critical role as terrestrial carbon sinks in mitigating climate change. However, accurate quantification of soil respiration ( R s )—the primary CO 2 efflux from forests—remains challenging due to existing studies' overreliance on annual‐scale estimates, which obscure fine‐scale spatiotemporal dynamics and key drivers of R s . Here, we developed a 500 m resolution monthly R s dataset for China's forests (2000–2020) using remote sensing data and a geographically weighted machine learning model. A geographically weighted extreme gradient boosting model achieved the highest accuracy in predicting monthly R s ( R 2 = 0.74, RMSE = 0.8 g C m −2 day −1 ). The mean total annual R s from 2000 to 2020 was 2.32 ± 0.09 Pg C year −1 , with summer contributing most and winter least. Annual total R s and seasonal total R s showed significant increasing trends across China's forests from 2000 to 2020, with the strongest increases in southern China's young/middle‐aged natural management forests and plantations. The relationships between R s and its driving factors varied: gross primary productivity (GPP) was the primary driver of annual R s across all forest management and age classes. Seasonally, temperature dominated R s in spring/winter, and GPP dominated summer R s across all forest management and age classes, while precipitation effects varied with management/age classes and season. Our findings highlight the necessity of monthly‐scale analysis and the significant role of forest management and age in modulating R s variability.

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Lightweight, superhydrophobic, and superelastic MXene/carboxymethylcellulose sodium composite aerogels for efficient and multifunctional electromagnetic interference shielding - Jiadong Li; Caiyun Liang; Chuanwei Lin; Yuna Wang; Yongjiu Liang; Dewen Dong (Chemical Engineering Journal, 2025)

Blocking the PD-1 signal transduction by occupying the phosphorylated ITSM recognition site of SHP-2 - Wenjie Li; Wenyi Mei; Hewei Jiang; Jie Wang; Xiaoli Li; Lina Quan; Yanyan Diao; Yanni Ma; Sisi Fan; Zhuwei Xie; Mengdie Gong; Huan Zhu; et al. (Science China Life Sciences, 2025)

Anchoring Ni atomic clusters on yolk-shell In2O3 microspheres for highly sensitive, ultra-rapid responding/recovering ppb-level NO2 detections - Zhidong Jin; Yue Mou; Jinbo Zhao; Fei Liu; Lin Liu; Dewen Zhao; Shiqiang Li; Jiurong Liu; Lili Wu (Chemical Engineering Journal, 2024)

Age dating of Paleocene Meirenfeng Formation and its significance for the hydrocarbon source rocks in the East China Sea basin - Huaizhi Xu; Weifeng Shen; Dewen Qin; Yun Liu; Bocheng Zhang; Chunming Lin; Xiyun Wang (Marine and Petroleum Geology, 2024)

Diversity and abundance of diazotrophic communities of seagrass Halophila ovalis based on genomic and transcript level in Daya Bay, South China Sea - Weiguo Zhou; Dewen Ding; Qingsong Yang; Juan Ling; Manzoor Ahmad; Xiancheng Lin; Liyun Lin; Ying Zhang; Junde Dong (Archives of Microbiology, 2021)

Rhizosphere microbiome dynamics in tropical seagrass under short-term inorganic nitrogen fertilization - Weiguo Zhou; Junde Dong; Dewen Ding; Lijuan Long; Anning Suo; Xiancheng Lin; Qingsong Yang; Liyun Lin; Yanying Zhang; Juan Ling (Environmental Science and Pollution Research, 2021)

Classification and 3-D distribution of upper layer water masses in the northern South China Sea - Jia Zhu; Quanan Zheng; Jianyu Hu; Hongyang Lin; Dewen Chen; Zhaozhang Chen; Zhenyu Sun; Liyan Li; Hao Kong (Acta Oceanologica Sinica, 2019)

Tide- and wind-driven variability of water level in Sansha Bay, Fujian, China - Hongyang Lin; Jianyu Hu; Jia Zhu; Peng Cheng; Zhaozhang Chen; Zhenyu Sun; Dewen Chen (Frontiers of Earth Science, 2017)

RKIP Regulates Neural Cell Apoptosis Induced by Exposure to Microwave Radiation Partly Through the MEK/ERK/CREB Pathway - Hongyan Zuo; Tao Lin; Dewen Wang; Ruiyun Peng; Shuiming Wang; Yabing Gao; Xinping Xu; Li Zhao; Shaoxia Wang; Zhentao Su (Molecular Neurobiology, 2015)

Ethylene increases accumulation of compatible solutes and decreases oxidative stress to improve plant tolerance to water stress in Arabidopsis - Mengying Cui; Yingchao Lin; Yuangang Zu; Thomas Efferth; Dewen Li; Zhonghua Tang (Journal of Plant Biology, 2015)